Age at menarche and risk of major cardiovascular diseases: Evidence of birth cohort effects from a prospective study of 300, 000 Chinese women. (15th January 2017) - Yang, Ling; Li, Liming; Millwood, Iona Y.; Peters, Sanne A.E.; Chen, Yiping; Guo, Yu; Bian, Zheng; Chen, Xiaofang; Chen, Lingli; Feng, Shixian; Lv, Silu; Pang, Zhigang; et al.
Abstract: Background: Previous studies of mostly Western women have reported inconsistent findings on the association between age at menarche and risk of cardiovascular disease (CVD). Little is known about the association in China where there has been a large intergenerational decrease in women's mean age at menarche. Methods: The China Kadoorie Biobank recruited 302, 632 women aged 30–79 (mean 50.5) years in 2004–8 from 10 diverse regional sites across China. During 7 years follow-up, 14, 111 incident cases of stroke, 14, 093 of coronary heart disease (CHD), and 3200 CVD deaths were reported among 281, 491 women who had no prior history of CVD at baseline. Cox regression yielded adjusted hazard ratios (HRs) relating age at menarche to CVD risks. Results: The mean (SD) age of menarche was 15.4 (1.9) years, decreasing from 16.2 (2.0) among women born before 1940 to 14.7 (1.6) for those born during the 1960s–1970s. The patterns of association between age at menarche and CVD risk appeared to differ between different birth cohorts, with null associations in older generations but U-shaped or weak positive associations in younger women, especially those born after the 1960s. After minimizing the potential confounding effects from major CVD risk factors, both early and late menarche, compared with menarche at age 13 years, were associated with increased risk of CVD morbidity and mortality, which was more pronounced in younger generations. Conclusion: Among Chinese women the associations between age at menarche and risk of CVD differed by birth cohort, suggesting other factors may underpin the association.